Amelioration of a sandy bris soil using condisoil™ for cultivation of kenaf (Hibiscus cannabinus L.) - Tijani, Akinbola Sheu (2020)
Soil fertility management is a pre-requisite for successfully growing kenaf in marginal soil. ‘CondiSoil’ is a soil amendment, formulated and patent filed by Lynas Malaysia Sdn Bhd., a rare earths mining and processing company in Malaysia. Hence, the objectives of this study were: (i) to determine the effect of different pH on dissolution of CondiSoil in a sandy beach ridges interspersed with swales (BRIS) soil using an open leaching system and (ii) to evaluate the effect of CondiSoil on growth performance and yield of kenaf cultivated on BRIS soil. For the dissolution experiment, ‘CondiSoil’ made of Water Leach Purification (WLP), Neutralization Underflow (NUF) residue and composted oil palm empty fruit (EFB) was applied to the BRIS soil in the column. The dissolution of ‘CondiSoil’ was measured in an open-leaching system using leaching solutions of different pH (1.2, 3.6, 4.6, 5.6 and 8.8) values. For the second experiment, a field trial was conducted at the experimental site of Ladang Kenaf, Taman Industri Teknologi Terengganu (TITT), National Kenaf and Tobacco Board (LKTN), Merang, Setiu, Terengganu. Two kenaf varieties ‘KB6’ (season 1) and ‘V36’ (season 2) were planted on BRIS soil applied with CondiSoil at the rate of 28 tons ha-1 in combination with a full (500 kg ha-1) and a half rate of recommended NPK fertilizer. The following treatments combination were used: (i) no CondiSoil + NPK (T1) (control); (ii) CondiSoil + NPK (T2); (iii) no CondiSoil + ½ NPK (T3) (control); and (iv) CondiSoil + ½ NPK (T4). In the second season, the treatments were split into with and without irrigation system. The growth and yield parameters were measured at growing stage and yield at harvest, respectively. The result of CondiSoil dissolution revealed that, most of the elements studied (P, Ca, Mg, Mn and Al) tend to be leached in higher concentrations in the earlier days, and gradually reduced by days, irrespective of the pH of leachant. Among the five leaching solutions used, there were significant differences (α = 0.05) in the cumulative quantity of phosphorus (P) dissolved at pH 1.2, 3.6 and 4.6 with the highest mean of 57.63 mg dissolved at pH 1.2. Considering the amount of ‘CondiSoil’ applied, only 66.2% (P), 73.5% (Ca) and 44.9% (Mg) was dissolved by pH 1.2 and 3.6 leachants at the end of the leaching studies (30-day). The results of field trial revealed that highest number of leaves, height growth, biomass for root, leaf, bast and core fibre of kenaf were obtained in T2, plot treated with CondiSoil + NPK, for both seasons; followed by T1, while T3 gave the poorest result. The results revealed that treatments do not have effect on the number of plants per hectare. Besides, further increase in NPK significantly lead to increased growth and biomass. Application of irrigation due to insufficient rainfall experienced in the pre-planting season did not have impact on the yield in the season 2, because of heavy downpour that was later experienced in the growing period. The dissolution characteristics of most elements from 'CondiSoil' studied in first experiment depend on the pH of the leaching solution. Only 0.5 and 0.3% of Th and Sr element, respectively was able to dissolve and leach at the end of 30 days. The field trial study reiterates the fact that additional amendments is needed for BRIS soils in Malaysia to yield better in terms productivity of any plant being grown on it due to the poor fertility level of the soil.